War on the EPA America's endangered environmental protections - Alley, William M. (Rowman & Littlefield, 2020)
This book examines the daunting hurdles facing the EPA in its critical roles in drinking water, air and water pollution, climate change, and toxic chemicals. It illustrates the importance of a strong EPA, the challenges of regulation, and how today's war on science is undermining the scientific foundation upon which the agency's legitimacy rests.